2023
DOI: 10.3390/nano13030505
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Sensing in All-Dielectric Metasurface Driven by Quasi-Bound States in the Continuum

Abstract: Quasi-bound states in the continuum (quasi-BIC) in all-dielectric metasurfaces provide a crucial platform for sensing due to its ability to enhance strong matter interactions between light-waves and analytes. In this study, a novel high-sensitivity all-dielectric sensor composed of a periodic array of silicon (Si) plates with square nanoholes in the continuous near-infrared band is theoretically proposed. By adjusting the position of the square nanohole, the symmetry-protected BIC and Friedrich–Wintgen BIC (FW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The red solid circles represent the coupled (or hybrid) mode based on the indirect coupling between GMR 1st and BIC 2nd , and they are obtained by fitting Fano formula to the reflection spectra of Figure 2a. The transmission in the Fano formula can be described as follows [56][57][58][59][60]:…”
Section: Validation Of the One-port Resonant System Mimickingmentioning
confidence: 99%
“…The red solid circles represent the coupled (or hybrid) mode based on the indirect coupling between GMR 1st and BIC 2nd , and they are obtained by fitting Fano formula to the reflection spectra of Figure 2a. The transmission in the Fano formula can be described as follows [56][57][58][59][60]:…”
Section: Validation Of the One-port Resonant System Mimickingmentioning
confidence: 99%
“…17 TMDs can be integrated into photonic structures such as plasmonic antennas, metasurfaces, and photonic crystals to achieve enhanced emission despite their low quantum yield and short light-matter-interaction length. [18][19][20][21][22][23][24][25] Hydrogenated amorphous silicon (a-Si:H) is extensively used for the fabrication of metasurfaces in wavelengths ranging from 660 nm to 1100 nm. Although many theoretical studies predicted high enhancement factors and exciton-polariton formation, [11][12][13][14] there are only a few experimental studies, where the quasi-BIC resonance of Si metasurface has been shown to produce emission enhancement in the visible wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…This mode allows electromagnetic wave energy to reside in the continuum for a long period of time [14]. The Q-BIC mode is easily recognized in the electromagnetic spectrum due to its Fano resonance characteristic with finite linewidth [15][16][17]. As for the methods for generating Q-BIC modes, there are two main approaches: periodic structure design and asymmetric structure design.…”
Section: Introductionmentioning
confidence: 99%